Association between risk factors of common noncommunicable diseases (diabetes, hypertension, and cardiovascular diseases) and sociodemographic factors in young adult women - Ankita Singh; Tapas Kumar Ray; Balraj Dhiman (Wolters Kluwer Medknow Publications, 2021)
Introduction: During the past 50 years, there is a substantial rise in noncommunicable diseases (NCDs) mortality in developing countries. India is also undergoing demographic transitions. Lifestyle which increases the risk of NCDs in younger age group will lead to increase in NCDs burden further in future generation. Objectives: The objective of this study is to determine the association between risk factors of common NCDs and sociodemographic factors in young adult women of Palam Village, New Delhi. Settings and Design: A community-based cross-sectional study was conducted in Palam Village, New Delhi. Materials and Methods: A total of 585 study participants were interviewed using a predesigned, semi-structured questionnaire. Waist circumference, blood pressure (BP), and weight were measured using nonstretchable measuring tape, digital BP apparatus, and digital weighing scale, respectively. Qualitative data are expressed in proportions and Chi-square test is applied. Mean and standard deviation are used for quantitative data. Results: As the socioeconomic status improved, the frequency of consuming adequate amount of fruits and vegetables in a day also increased. This association was statistically significant (P < 0.05). Conclusion: The present study reported varied prevalence of different risk factors with various sociodemographic characteristics and there is an urgent need to implement population, individual, and program wide prevention and control interventions.